IMPACT OF ORGANIZATIONAL COMMITMENTS TO PERFORMANCE OF DOSE HIGHER EDUCATION OF ISLAMIC PRIVATE VOCATIONAL SCHOOL IN MEDAN - Zulia Hanum; Iskandar Muda; Rina Bukit; Muhyarsyah Muhyarsyah (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to determine the effect of commitment on the performance of lecturers in Private Universities in Medan City. The research method used was a survey. The sample of this study is 90 PTS lecturers and taken by random technique. From the results of the study, it can be concluded that: there is an influence on the performance of the lecturer.